Proteção à vítima e à prova testemunhal: eficácia jurídica contra a impunidade - Morais, Maiza Helena Rodrigues (2014)
The aim of the present research is to analyze the performance of the protection program to endangered victim and witness – PROVITA/ Amazonas, considering its juridical efficiency in State of Amazonas, in the period between the years 2012 and 2013. So it was analyzed the data enclosed in the Work Plan of each one of the specified years, as well the recorded results in the Object Fulfillment report. The PROVITA sprang from civil society’s movements and group experiences that thought in this kind of protection strategy to combat the impunity and effectively collaborate with the pursuit for justice. From this movement the Federal Law 9.807/99 was created, which institutes the program and its guidelines. This foundation originated the state legislation and the rest of practices that today are added to the actions that seek the real condemnation of the accused people in those processes which exist the protected witnesses/victim participation, offering to this public all the necessary structure to have the conditions to effectively contribute with their testimonies. This protection politic fits with the public security politic which charted guidelines in its national plan to improve and potentize these actions faced to endangered victims and witnesses. The methodology used was the documentary and bibliographic research, and a sample interview to validate the data.From the colected data, the technical-didactics limitation of the reasearched documents, as they have limited content and few objective, what embrass a more qualified analysis. Notwithstanding, it can be concluded that the Protection Program is effective in case of attend, in its majority, the emphasized criterions in the work plan, leaving gaps in the aspects related to procedural analysis, considering the work plan data come forward insufficient for this discussion